Cyclodextrins and polymers towards applications - H. J. Buschmann; E. Schollmeyer; L. Mutihac (ՀՀ ԳԱԱ հրատ.)
Miscellaneous possibilities are known to bring cyclodextrins and polymers together.
Keywords: Biology; Biochemistry